Prothrombin induced by vitamin K Absence-II versus alpha-fetoprotein in detection of both resectable hepatocellular carcinoma and early recurrence after curative liver resection: A retrospective cohort study - Wang, Ming-Da; Sun, Li-Yang; Qian, Guo-Jun; Li, Chao; Gu, Li-Hui; Yao, Lan-Qing; Diao, Yong-Kang; Pawlik, Timothy M.; Lau, Wan Yee; Huang, Dong-Sheng; Shen, Feng; Yang, Tian (International journal of surgery (London, England), 2022)
Alpha-fetoprotein (AFP) and prothrombin induced by vitamin K absence-II (PIVKA-II) are two commonly used biomarkers for detection and prognostic prediction of hepatocellular carcinoma (HCC). This study sought to evaluate and compare the use of these two biomarkers to detect HCC, as well as predict postoperative early recurrence (within 2 years after HCC resection). Data on consecutive patients who underwent curative resection for HCC between 2014 and 2020 was prospectively collected and reviewed. Serum AFP and PIVKA-II levels within one week before surgery or at the time of detection of early recurrence were assessed; preoperative AFP positivity (≥20 ng/ml) and preoperative PIVKA-II positivity (≥40 mAU/ml) were examined relative to recurrence using univariate and multivariate Cox-regression analyses. Among 751 patients who underwent curative HCC resection, 589 (78.4%) patients had preoperative PIVKA-II positivity versus 498 (66.3%) patients had preoperative AFP positivity (P < 0.001). With a median follow-up of 41.6 months, 370 (50.1%) patients had an early HCC recurrence; among patients with an early recurrence, the proportion of patients with PIVKA-II positivity versus AFP positivity (76.5% vs. 60.0%, P = 0.002) was higher. On multivariate analysis, preoperative PIVKA-II positivity, but not preoperative AFP positivity was an independent risk factor to predict early recurrence after HCC resection. AFP and PIVKA-II are useful biomarkers to detect resectable HCC and predict early recurrence after HCC resection, with the latter showing higher rates of positivity. Preoperative PIVKA-II positivity was independently associated with early recurrence following HCC resection. [Display omitted] •Compared with AFP, PIVKA-II is more sensitive in detection of resectable HCC.•PIVKA-II is more useful than AFP to detect post-epatectomy recurrent HCC.•Preoperative PIVKA-II is independently associated with early recurrence after HCC resection.